Refining the mechanism of heme acquisition from free hemoglobin by Staphylococcus aureus IsdH - Valeria Buoli Comani; Omar De Bei; Giulia Paris; Marialaura Marchetti; Francesca Pancrazi; Barbara Campanini; Luca Ronda; Ben F. Luisi; Serena Faggiano; Anna Rita Bizzarri; Stefano Bettati (Proceedings of the National Academy of Sciences, 2026)
Staphylococcus aureus is a human pathogen whose virulence depends on iron acquisition. The bacterium expresses the hemophores IsdB and IsdH that enable heme capture from host hemoglobin (Hb). Unlike IsdB, IsdH can bind both free Hb and Hb:haptoglobin (Hb:Hp) complexes. Here, we present a comprehensive structural analysis of full-length IsdH in complex with free Hb, overcoming the limitations of previous studies based on truncated IsdH constructs. Cryo-EM revealed a previously unobserved oligomeric state and a unique binding pose of the N-terminal Hb-binding domain, likely representing the initial step of Hb engagement. Time-resolved and single-molecule force spectroscopy experiments delineated the sequential steps and mechanical aspects of Hb binding and heme extraction. Together, these findings provide an integrated structural and functional view of the IsdH–Hb interaction in the absence of Hp, as may occur during hemolysis, and offer insights into S. aureus heme scavenging and potential avenues for therapeutic inhibition.